An emotional high: Utilizing emotion-based decision-making to boost messaging impact in B2B sales. Issue 9 (3rd August 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Emotional sales and advertising practices have tended to be used best in B2C sales. Yet new research is showing how these same practices are hugely beneficial in B2B sales as well. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.